Influence of endotoxin treatment on dexamethasone induction of hepatic phosphoenolpyruvate carboxykinase. - McCallum, R E (1983)
Decreased glucocorticoid binding has been observed at a time after endotoxin (3 to 6 h) when imparied liver enzyme induction is known to occur. This study was undertaken to characterize the early time course of hypoglycemia and decreased liver phosphoenolpyruvate carboxykinase (PEPCK) activity in intact and adrenalectomized mice given endotoxin. In addition, altered steroid induction of hepatic PEPCK was examined in adrenalectomized mice given dexamethasone at intervals before and after a median lethal dose of endotoxin. Intact mice demonstrated a dramatic hyperglycemia at 1 h after endotoxin treatment, a response absent in adrenalectomized mice. Plasma glucose levels were significantly reduced from control values at 3 and 6 h posttreatment, with the most pronounced endotoxin-induced hypoglycemia seen in adrenalectomized mice. Hepatic PEPCK activity in intact mice given endotoxin was decreased at 3 and 6 h after treatment, although no change from basal, noninduced levels was seen in poisoned adrenalectomized mice. The increased increment in hepatic PEPCK activity due to fasting of intact control mice was reproduced in adrenalectomized control mice by the administration of dexamethasone. Furthermore, the induction of hepatic PEPCK by dexamethasone was inhibited by 1 h after endotoxin treatment, with enzyme activity falling to basal, noninduced levels by 6 h posttreatment. At these same time intervals after endotoxin treatment, no evidence of histopathology in the liver or adrenal glands was seen. These results coincide with changes in steroid binding seen previously and indicate that endotoxin treatment produces significant alterations in glucocorticoid action at the subcellular or molecular level.